About Italian Futurism in Rijeka on 1919 - Lukežić, Irvin (Poznańskie Studia Slawistyczne, 2020)
The article discusses the short-lived emergence of Italian futurism in Rijeka, just after the end of World War I, in the context of the political adventure of Gabrielle DʼAnnunzio, who, with the help of his supporters, an ardite, tried to annex the city to the Kingdom of Italy. At that moment, the avant-garde spirit of Italian futurism could manifest itself here in all its main features: activism, antagonism, nizilism and agonism. In addition to the founder of Italian futurism, Filippo Tommas Marinetti, Mario Carli, Guido Keller and Giovanni Comisso stayed and worked in Rijeka during 1919. The article seeks to describe their actions on the basis of newspaper reports in the Rijeka daily La Vedetta dʼItalia.